Visualization and Characterization of the Brain Regional Heterogeneity of Astrocyte–Astrocyte Structural Interactions by Using Improved Iontophoresis with Dual-Fluorescent Dyes - Qingran Li; Bin Zhou; Mengchan Su; Ping Liao; Fan Lei; Xin Li; Daqing Liao; Xia Zhang; Ruotian Jiang (Brain Sciences, 2023)
Astrocytes are morphologically intricate cells and actively modulate the function of the brain. Through numerous fine processes, astrocytes come into contact with neurons, blood vessels, and other glia cells. Emerging evidence has shown that astrocytes exhibit brain regional diversity in their morphology, transcriptome, calcium signaling, and functions. However, little is known about the brain regional heterogeneity of astrocyte–astrocyte structural interaction. So far, the visualization and characterization of the morphological features of adjacent astrocytes have been difficult, and as a result, it is still well-accepted that astrocytes in the adult brain share non-overlapped territory. In contrast, employing an approach that combines viral labeling with dual-fluorescent dyes iontophoresis under brightfield and imaging using confocal microscopy allows for the efficient and specific labeling of adjacent astrocytes, enabling a comprehensive visualization of their fine processes and the degree of their territorial overlap. Our study in the hypothalamic regions of the brain revealed a marked spatial overlap among adjacent astrocytes, which differs from the conventional understanding based on more extensively studied regions, like the hippocampus. Additionally, we revealed the heterogeneity of the astrocyte–neuron ratio across brain regions and conducted an assessment of the photostability and labeling efficiency of fluorescent dyes used for labeling adjacent astrocytes. Our study provides new insights for studying the morphological heterogeneity of astrocytes across the central nervous system.